Antioxidant activities and oxidative stress inhibitory effects of ethanol extracts from Cornus officinalis on raw 264.7 cells. Issue 1 (December 2016) - Hwang, Kyung-A; Hwang, Yu-Jin; Song, Jin
Abstract Background Cornus officinalis, is a deciduous tree native to the eastern Asia, distributes mainly in (e.g. Korea, as well as China, and Japan). It is used as folk medicine to backache, polyuria, hypertension and nervous breakdown. Pharmacological studies have demonstrated thatC. officinalis possess anti-oxidant, anti-hyperglycemic, and immune regulatory effects. However, reports on the antioxidant activity ofC. officinalis have been limited toin vitro radical scavenging studies. Its mechanism of action within the cell at the genetic level especially has not yet been clearly defined. Therefore, we investigated the anti-antioxidant activities ofC. officinalis in RAW 264.7 cells. Methods The antioxidant activities and protective effects ofC. officinalis ethanol extract on cell damage and the antioxidant enzyme system in lipopolysaccharide (LPS)-induced oxidative stress-damaged RAW 264.7 cells were assessed. To measure the effects ofC. officinalis on antioxidant activities, we used the following methods: Total phenol and flavonoid contents, DPPH scavenging activity assay, ABTS scavenging activity assay, FRAP value measurement, xanthine oxidase activity assay, ROS generation measurement and real time PCR. Results The total phenol and flavonoid contents ofC. officinalis extracts were 27.04 mg GAE/g and 3.70 mg QE/g, respectively. The antioxidant activities ofC. officinalis extracts increased in a dose-dependent manner: the IC50 values for DPPH and ABTS radical scavenging activities ofC. officinalis extracts were 99.32 μg/mL and 138.51 μg/mL, respectively.C. officinalis extracts inhibited xanthine oxidase activity and reactive oxygen species generation. The expression of antioxidant enzymes, Cu/ZnSOD, MnSOD, catalase, and glutathione peroxidase increased upon treatment withC. officinalis extracts at 100 μg/mL, compared to that in the LPS-treated group. Conclusions These results suggest the therapeutic potential ofC. officinalis extract as an anti-oxidant agent.